PERBEDAAN MODIFIKASI LARUTAN ZnS (Zinc sulfite) DENGAN NaCl (Natrium Cloride) 0.9 % METODE FLOTASI TERHADAP JUMLAH TELUR CACING Soil Transmitted Helminth (STH) - Siregar, Saadah; Manurung, Arnita Elisabet; Rizky, Vincentia Ade; Krisdianilo, Vinsensius (Jurnal Laboratorium Khatulistiwa, 2024)
Worms is a disease caused by the entry of parasites in the form of worms into the human body due to the influence of environmental factors or food that is not kept clean. Factors that cause the risk of helminthiasis in humans include food that is infected with worm eggs, feet that are in direct contact with soil containing worm vectors because they do not wear footwear, the habit of defecating in random places, availability of clean water, hand washing, washing habits. plates, And nail hygiene. The purpose of this study was to determine the difference in the number of worm eggs to be found using ZnS 1% and NaCl 0.9% solution using the flotation method. The data obtained from faecal examination using the flotation method with ZnS 1% and NaCl 0.9%, namely Soil Transmitted Helminth (STH) worm eggs, then the number of eggs will be presented in table form and analyzed descriptively. Result With the average yield of worm eggs found in  a solution of ZnS  1% and NaCl 0.9% using the flotation method for the number of Soil Transmitted Helminth (STH) worm eggs. In ZnS 1% solution the average is 2.12 with 4 Ascaris lumbricoides eggs, Trichuris trichura 2 and 3 hookworms while in 0.9% NaCl solution the average is 1.31 with 5 Ascaris lumbricoides worm eggs, Trichuris trichura 1 and worms mine 1. The Manny Whitney statistical test showed results of Sig 0.003 (P<0.005), so it was concluded that there was a difference in the number of STH worm eggs found using ZnS 1% solution and 0.9% NaCl using the flotation method.